PEMBINAAN DISIPLIN GURU UNTUK MEMPERBAIKI PEMBELAJARAN - Sirmanto Sirmanto; Rohiat Rohiat; Aliman Aliman (Manajer Pendididikan, 2017)
The purpose of this study was to determine whether the coaching by the school head can improve the discipline of teachers in preparing teaching and program Elementary School 12 South Bengkulu learning. The specific objective to increase discipline in developing the syllabus, lesson plan and program assessment. The method used is action research school, with study subjects were 12 elementary school teachers from South Bengkulu. The results of this study indicate that coaching by the school head can improve discipline and ability of teachers to develop learning programs.